Improving Access to the Glycated Hemoglobin Test in Rural Communities With Point-of-Care Devices: An Application Study - Camargo, Marianne Silveira; Passos, Luiz Carlos Santana; Mistro, Sostenes; Soares, Daniela Arruda; Kochergin, Clavdia Nickolaevna; Carvalho, Vivian Carla Honorato dos Santos de; Macedo, Jéssica Caline Lemos; Cortes, Taciana Borges Andrade; Souza, Amós Alves de; Rumel, Davi; Oliveira, Marcio Galvão (Frontiers in Medicine, 2021)
Background: Living in a rural or remote area is frequently associated with impaired access to health services, which directly affects the possibility of early diagnosis and appropriate monitoring of diseases. Objective: To evaluate the application of point-of-care technology for glycated hemoglobin (HbA1c) estimation and identification of new diagnoses of diabetes in primary care among rural communities in a Brazil. Materials and Methods: We included individuals aged 18 years or older among rural communities in a Brazilian municipality. Participants were assessed for anthropometrics, blood pressure, and capillary glycemia during routine primary care team activities at health fairs and in patient groups. Participants previously diagnosed with diabetes but without recent HbA1c test results or those without a previous diagnosis but with random capillary blood glucose levels higher than 140 mg/dL were tested for HbA1c by using a point-of-care device. Results: Of the 542 individuals without a previous diagnosis of diabetes, 73 (13.5%) were positive for capillary glycemia. Of these 73, 31 (42.5%) had HbA1c levels that were considered indicative of prediabetes and 16 (21.9%) were newly diagnosed with diabetes. Among 313 patients who were previously diagnosed with diabetes, recent HbA1c results were unavailable for 210. These individuals were tested using point-of-care devices. Among them, 143 (68.1%) had HbA1c levels higher than target levels. Conclusion: The application of point-of-care devices for HbA1c level measurement improved the access to this test for people living in rural areas. Thus, it was possible to include this technology in the routine activities of primary health care teams.